2022
DOI: 10.1186/s12882-022-02783-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation of KCNJ1 identified in an affected child with nephrolithiasis

Abstract: Nephrolithiasis is not common in children, but the incidence is gradually increased in these years. Urinary tract malformations, urinary infection, dietary habits, geographic region and genetic factor are involved in the etiology of nephrolithiasis. For the affected child, it is especially important to elucidate the etiology, which may provide an accurate diagnosis, a personalized therapy and effective follow-up strategy. Here to seek the etiology of a ten-year-old boy incidentally found with nephrolithiasis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Similarly, a previous study declared that GFAP was associated with poor outcomes in BC patients ( 54 ). KCNJ1 participated in potassium balance, and its mutation was able to trigger Bartter syndrome ( 55 ). In clear cell renal cell carcinoma, the results indicated that this gene was highly expressed in normal tissue samples and produced an inhibitory role in ccRCC progression ( 56 ), while there was a lack of reports about its role in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study declared that GFAP was associated with poor outcomes in BC patients ( 54 ). KCNJ1 participated in potassium balance, and its mutation was able to trigger Bartter syndrome ( 55 ). In clear cell renal cell carcinoma, the results indicated that this gene was highly expressed in normal tissue samples and produced an inhibitory role in ccRCC progression ( 56 ), while there was a lack of reports about its role in BC.…”
Section: Discussionmentioning
confidence: 99%